A Study on Effects of Biotic Resources on a Prey-Predator Population - Mandal, Manotosh; Jana, Soovoojeet; Nandi, Swapan Kumar; Kar, T. K. (Discontinuity, Nonlinearity, and Complexity, 2026)
The environmental carrying capacities for the prey population and the predator population are restricted by their availability of foods. In this article, we introduce a prey-predator type ecological model in which the prey and predator have different biotic resources for food. Therefore the suggested predator-prey model depends on the ratio-dependent ecological model which can be applied in the study of food chains. The details dynamical behaviour of the proposed model has been carried out. The different bifurcations and numerical analyzes are demonstrated to illustrate the dynamical behavior of our proposed model system.